Impact of diabetes on clinical outcome of patients with heart failure undergoing ICD and CRT procedures: results from the German Device Registry. (18th February 2020) - Kaya, Elif; Senges, Jochen; Hochadel, Matthias; Eckardt, Lars; Andresen, Dietrich; Ince, Hüseyin; Spitzer, Stefan G.; Kleemann, Thomas; Maier, Sebastian S.K.; Jung, Werner; Stellbrink, Christoph; Rassaf, Tienush; et al.
Abstract: Aims: Diabetes mellitus (DM) has a negative impact on prognosis in patients with heart failure (HF). The role impact of DM in HF patients with implantable cardioverter defibrillator (ICD) or cardiac resynchronization therapy (CRT) devices might differ and remains unclear. The aim of our study was to investigate the impact of DM on periprocedural complications and clinical outcome in HF patients undergoing ICD or CRT implantation. Methods and results: Within the German Device Registry, data from 50 German centres were collected between January 2007 and February 2014. A retrospective analysis of n = 5329 patients undergoing ICD implantation was conducted. Patients' characteristics, procedural data, periprocedural complications, and post‐procedural clinical outcome, including a composite clinical endpoint of all‐cause mortality, stroke, and myocardial infarction (MACCE), were analysed. Subgroup analysis were performed for ICD and CRT implantations. Median follow‐up was 15.7 (12.9; 20.0) and 16.2 (12.8; 21.2) months in DM and non‐DM patients. Of 5329 patients enrolled, n = 1448 (27.2%) had a diagnosis of DM. Within the cohort, 94% of DM and 90% of non‐DM patients had a diagnosis of HF. Patients with DM were older, had higher body mass index, and higher rate of cardiovascular comorbidities compared with non‐DM patients. Unadjusted and adjusted analyses revealed similar all‐over intrahospital periprocedural complication rates in both groups (4.1% vs 3.9%). Unadjusted Kaplan–Meier survival analysis showed higher all‐cause mortality after 1 year (9.0% vs 6.3%; log‐rank P = 0.001) with higher MACCE rates (10.0% vs 7.3%; P < 0.001) in the DM group versus non‐DM patients. After multivariable adjustment for relevant covariates, the association of DM to MACCE disappeared [HR 1.11 (0.89‐1.38)]. Because chronic kidney disease (CKD) was clearly associated with increased 1 year MACCE after multivariate adjustment [odds ratio (OR) 2.11 (1.68–2.64)], a subgroup analysis was performed showing a strong trend towards more perioperative complications in DM patients with CKD [OR 2.16 (0.9–5.21)], while no effect of DM was observed in patients without CKD [OR 0.73 (0.42–1.28)]. Conclusions: The overall risk of periprocedural complications and short‐term (1 year) clinical outcome in patients with DM and HF undergoing ICD or CRT defibrillator (CRT‐D) implantation was not increased. In contrast, CKD was associated with an increased risk of 1 year MACCE in HF patients undergoing ICD/CRT‐D implantation.